IMPLEMENTASI MONITORING LOKASI DAN GROUP SHARING BERBASIS ANDROID - Supriyanto Karya (Jurnal Informatika dan Bisnis, 2017)
Along with the increase in business processes,Â  makes everyone to have a dense schedule of activities. This increase was followed by the development of the technology world is so fast that requires every person to be able to utilize existing technology in all daily activities. Because the activities are so dense, resulting in everyone's hard to know where each other for such a purpose as well as in the affairs of a job that requires a supervisor to monitor the location of his men. For that proposed an application that can be used as a tool for monitoring the location and to provide location information of a place as a supporter. To build an application system monitoring locations, the authors use a variety of theories related to geographic information systems and GPS technology as a reference. This application was developed by utilizing GPS technology and implementing google maps as a basis for the development of applications that are built on smartphones with Android operating system that open-source.The results from this research is an application monitoring the location and group sharing to facilitate a person to monitor the location of others, support for communications of a group or organization in an activity and provide location information to the public somewhere.The conclusion of this research is the application of monitoring locations and group sharing can facilitate someone in monitoring locations, support groups or organizations to communicate and provide a useful location information.Keywords: Monitor Location, Maps, Group Sharing